2015
DOI: 10.1111/ddi.12391
|View full text |Cite
|
Sign up to set email alerts
|

Predicting invasiveness of species in trade: climate match, trophic guild and fecundity influence establishment and impact of non‐native freshwater fishes

Abstract: Aim Impacts of non-native species have motivated development of risk assessment tools for identifying introduced species likely to become invasive. Here, we develop trait-based models for the establishment and impact stages of freshwater fish invasion, and use them to screen non-native species common in international trade. We also determine which species in the aquarium, biological supply, live bait, live food and water garden trades are likely to become invasive. Results are compared to historical patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 68 publications
5
97
2
1
Order By: Relevance
“…Currently, 20% of finfishes with highest aquaculture production (> 25 000 t year À1 ) are foreign to China and some dominate present-day fish communities in southern China (Wang et al, 2014;Xing et al, 2015). The risk of non-native species should therefore be systematically assessed before their introductions (Howeth et al, 2016), especially in developing countries where megadiverse biotas are chronically under-protected by current conservation policies. For example, a decree referred to as the 'Tilapia Law' had been issued in Brazil to improve aquaculture production by naturalizing non-native fish in Amazonian River Basin (Padial et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 20% of finfishes with highest aquaculture production (> 25 000 t year À1 ) are foreign to China and some dominate present-day fish communities in southern China (Wang et al, 2014;Xing et al, 2015). The risk of non-native species should therefore be systematically assessed before their introductions (Howeth et al, 2016), especially in developing countries where megadiverse biotas are chronically under-protected by current conservation policies. For example, a decree referred to as the 'Tilapia Law' had been issued in Brazil to improve aquaculture production by naturalizing non-native fish in Amazonian River Basin (Padial et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…; Howeth et al . ). Carrete and Tella () also demonstrated that wild‐caught bird species traded as exotic pets were more likely to establish non‐native populations than captive‐bred species.…”
Section: Which Exotic Pets Will Establish Non‐native Populations Next?mentioning
confidence: 97%
“…For the 32 alien fishes and the 144 drainages, we gathered information on 12 geographical, environmental and species‐specific covariates consistently reported in the literature to be associated with the establishment of alien fishes (Clavero, ; García‐Berthou et al., ; Howeth et al., ; Liew, Carrasco, Tan, & Yeo, ). The covariates are described in Table and were collected from publications and online databases (Domisch, Amatulli, & Jetz, ; Froese & Pauly, ; Jetz, McPherson, & Guralnick, ; Kriticos et al., ; Wildlife Conservation Society & Center for International Earth Science Information Network, ).…”
Section: Methodsmentioning
confidence: 99%